African music activities of the Department of Ethnomusicology at the Ethnographical Museum of Berlin (West) by Prof. Dr. Artur Simon - Simon, Artur (International Library of African Music, 1987)
The highlights of our concert activities in June 1984 were the second invitation to three former Buganda court musicians, Evaristo Muyinda, Ludvico Sserwanga and Hadisoni Kiyaga, and the first performance of the famous jali and kora-player, Jali Nyama Suso from Gambia.
Keywords: African Music